2019
DOI: 10.1159/000495562
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Cutoff Scores for Dementia and Mild Cognitive Impairment in the Brazilian Version of the Montreal Cognitive Assessment among the Elderly

Abstract: Objective: To propose cutoff scores for the Brazilian version of the Montreal Cognitive Assessment (MoCA-BR) stratified by education in order to detect mild cognitive impairment (MCI) and mild Alzheimer’s disease (AD) in the elderly. Method: A transversal study in health centers was performed on 159 elderly people with 4–12 years of education and 70 of their peers with over 12 years of schooling. The MoCA-BR cutoff scores for screening cognitive impairment were determined based on an ROC curve analysis. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
(71 reference statements)
5
14
0
1
Order By: Relevance
“…is wide range of MoCA scores (i.e., 18-24) for uncertain MCI from this study reflects the wide range of MoCA cutoffs found previous studies that used certain validating criteria and ROC analysis [2][3][4][5][6][7][8][9][10][11][12]. Studies that used latent class analysis also found cutoffs within a similar range, for instance, 19-25 [27] and 19-23 [28].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…is wide range of MoCA scores (i.e., 18-24) for uncertain MCI from this study reflects the wide range of MoCA cutoffs found previous studies that used certain validating criteria and ROC analysis [2][3][4][5][6][7][8][9][10][11][12]. Studies that used latent class analysis also found cutoffs within a similar range, for instance, 19-25 [27] and 19-23 [28].…”
Section: Discussionsupporting
confidence: 68%
“…e optimal cutoff score for screening mild cognitive impairment (MCI) in older adults has been widely explored in applying the Montreal Cognitive Assessment (MoCA), which is a tool designed exclusively for screening MCI in older adults [1]. Nevertheless, different from the original cutoff score of 24, various cutoffs have been identified, ranging from 18/19 to 26/27 across different cultures [2][3][4][5][6]. A recent meta-analysis of studies with strictly verifiable criteria of MCI suggested that the optimal cutoff was 23 based on balanced sensitivity (the probability of true positives) and specificity (the probability of true negatives) as well as samples of different language, cultural, and educational background.…”
Section: Introductionmentioning
confidence: 99%
“…MoCA scores range between 0 and 30; a score of ≥ 26 reflects a lack of cognitive difficulties. The cut‐off scores of 22 points are recommended in the case of individuals aged 70+ (Pinto et al., 2019). Younger subjects with scores < 26 and older subjects with scores < 21 were not taken into account in the study. Vocabulary subtest of the Polish version of Wechsler Adults Intelligence Scale (WAIS‐R PL; Brzeziński et al., 2004).…”
Section: Methodsmentioning
confidence: 99%
“…MoCA scores range between 0 and 30; a score of ≥ 26 reflects a lack of cognitive difficulties. The cut-off scores of 22 points are recommended in the case of individuals aged 70+(Pinto et al, 2019).ParticipantsAn invitation to participate in the study was posted on a local academic institution's website. The trials were carried out by two clinical psychologists.…”
mentioning
confidence: 99%
“…One of the most widely used brief assessment instruments is the Mini-Mental State Examination (MMSE) [14]. However, recent studies have found that it is not as sensitive in assessing MCI [5,[15][16][17][18][19] and early dementia as the Montreal Cognitive Assessment (MoCA), for which studies identify greater sensitivity and specificity to detect the stages mentioned above [13,[20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%